2013
DOI: 10.1111/tbed.12174
|View full text |Cite
|
Sign up to set email alerts
|

The Socioeconomic Impacts of Clinically Diagnosed Haemorrhagic Septicaemia on Smallholder Large Ruminant Farmers in Cambodia

Abstract: Haemorrhagic septicaemia (HS) is an acute fatal infectious disease of mainly cattle and buffalo and outbreaks occur commonly in Cambodia. Disease outbreak reports were examined to select five villages from three provinces for a retrospective investigation of HS epidemiology and socioeconomic impact on smallholders, with an aim of identifying potential benefits from improving disease prevention through biosecurity and vaccination. The Village Animal Health Worker (VAHW) or Chief in each village and 66 affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…A key component of community consultation is farmer discussions to confirm key animal health problems (Jones et al, 1998;Leyland & Catley, 2002). HS has traditionally been a major disease of concern due to high mortality rates and socioeconomic impacts, whereas the low mortality rates associated with FMD have made it a lower priority for farmers (Kawasaki, Young, Suon, Bush, & Windsor, 2015;Young, Suon, Andrews, Henry, & Windsor, 2013). However, studies indicate that smallholder farmers are becoming more aware of the production costs associated with an FMD outbreak (Young et al, 2013).…”
Section: Promoting Improved and Regular Two-way Communication Betweenmentioning
confidence: 99%
“…A key component of community consultation is farmer discussions to confirm key animal health problems (Jones et al, 1998;Leyland & Catley, 2002). HS has traditionally been a major disease of concern due to high mortality rates and socioeconomic impacts, whereas the low mortality rates associated with FMD have made it a lower priority for farmers (Kawasaki, Young, Suon, Bush, & Windsor, 2015;Young, Suon, Andrews, Henry, & Windsor, 2013). However, studies indicate that smallholder farmers are becoming more aware of the production costs associated with an FMD outbreak (Young et al, 2013).…”
Section: Promoting Improved and Regular Two-way Communication Betweenmentioning
confidence: 99%
“…FMD was the disease most likely to be reported by VAHW's at ~83%, with HS close behind at ~81% (Stratton, ). However, underreporting of FMD and HS cases is known to occur in Cambodia (Shankar et al., ; Vergne et al., ; Kawasaki et al., ; Young et al., ) and is also likely throughout the GMS. A two‐source capture–recapture analysis for estimating the true number of villages experiencing clinical FMD in 2009 was conducted in Svay Rieng province in Cambodia (Vergne et al., ), evaluating the reporting rate to provincial authorities at 0.05 (95% CI 0.03–0.13).…”
Section: Introductionmentioning
confidence: 99%
“…) and HS in Cambodia (Kawasaki et al . ) confirm that routine vaccination for priority large ruminant diseases is a cost‐effective disease management strategy. A previous study on the cost of FMD in Laos indicated that each dollar invested potentially achieved USD 5 in benefits (Nampanya et al .…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, despite lack of veterinary services and lab diagnostics, valuable financial impact data can be obtained from studies of clinically diagnosed disorders in developing countries, with HS in Cambodia as an example (Kawasaki et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation